From Law on the Books to Law in Action: Legal Protection for Women Victims of Physical Sexual Harassment under Indonesia’s UU TPKS - Arina Silviana; Bahtiar Tamrin; Arif Rohman (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
This study examines the implementation of legal protection for women victims of physical sexual harassment in Buol Regency under Law No. 12 of 2022 on Sexual Violence Crimes (UU TPKS). Using a socio-legal approach, the research combines normative legal analysis with empirical inquiry to assess how the law operates in practice and to identify the factors affecting victims’ access to justice, protection, and recovery. The findings reveal a significant gap between the victim-centered principles embodied in the UU TPKS and their implementation at the local level. Legal protection is often limited to procedural compliance, while substantive justice remains constrained by limited institutional capacity, fragmented service coordination, evidentiary difficulties, and restricted access to medical and psychosocial services. In addition, socio-cultural factors such as patriarchal norms, stigma, and informal dispute resolution practices discourage victims from reporting cases and weaken formal legal mechanisms. These formal and informal barriers interact within institutional practices, reinforcing discretionary decision-making and victim-blaming attitudes. The study concludes that although the UU TPKS provides a progressive normative framework for protecting women victims of sexual violence, its effectiveness depends on strengthening institutional capacity, improving trauma-informed services, enhancing inter-agency coordination, and promoting broader socio-cultural change, particularly in non-metropolitan regions.